2012
DOI: 10.1155/2012/732027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes and Hyperglycemia on Survival in Advanced Breast Cancer Patients

Abstract: Purpose. We examined the impact of diabetes and hyperglycemia on cancer-specific survival of patients with metastatic or recurrent breast cancer (BC). Methods. We performed a retrospective analysis of 265 patients with advanced BC receiving palliative chemotherapy. BC-specific mortality was compared for diabetic and nondiabetic patients as well as for patients that presented hyperglycemia during treatment. Results. No difference was observed between the diabetic and nondiabetic patients in terms of overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 19 publications
3
71
2
Order By: Relevance
“…Moreover, clinical epidemiological studies have shown that breast tumor progression and response to therapy differ between women with and without diabetes (4, 7, 10). The presence of a high glucose level, corresponding to hyperglycemia in vivo, has been reported to modulate breast cancer cell functions including survival, growth, and proliferation, suggesting the glucose level as being critical for breast cancer progression in patients with diabetes (11)(12)(13)(14)(15)(16)(17)(18)(19). Our previous studies also demonstrated that the migratory ability of MCF-7 human breast cancer cells, which is linked to invasion and metastasis, was strongly dependent on glucose concentration (13,14).…”
mentioning
confidence: 77%
“…Moreover, clinical epidemiological studies have shown that breast tumor progression and response to therapy differ between women with and without diabetes (4, 7, 10). The presence of a high glucose level, corresponding to hyperglycemia in vivo, has been reported to modulate breast cancer cell functions including survival, growth, and proliferation, suggesting the glucose level as being critical for breast cancer progression in patients with diabetes (11)(12)(13)(14)(15)(16)(17)(18)(19). Our previous studies also demonstrated that the migratory ability of MCF-7 human breast cancer cells, which is linked to invasion and metastasis, was strongly dependent on glucose concentration (13,14).…”
mentioning
confidence: 77%
“…Insulin resistance prior to cancer treatment was identified as an independent negative factor influencing overall survival, progression-free survival and development of treatment resistance in various cancer types [28,[77][78][79][80][81][82]. A retrospective study in 130 lymphoma patients identified high fasting blood glucose levels at diagnosis as a predictor of decreased overall-and progression-free survival [77].…”
Section: Influence Of Insulin and Glucose Levels On Therapy Efficacymentioning
confidence: 99%
“…Furthermore, a study in 1734 prostate cancer patients with localised disease treated with radical prostatectomy or radiation therapy identified glucose levels at time of diagnosis as an independent predictor of recurrence [78]. Moreover, high glucose levels in non-diabetic as well as diabetic patients with metastatic or recurrent breast cancer treated with palliative chemotherapy decreased overall survival [79]. An association between high pre-cancer treatment fasting blood glucose levels and the development of treatment resistance was observed in a population of 202 breast cancer patients treated with trastuzumab [80].…”
Section: Influence Of Insulin and Glucose Levels On Therapy Efficacymentioning
confidence: 99%
“…globulins. Also hyperglycaemia has been associated with increased risk of developing cancer, among others breast cancer [200], as well as a poor breast cancer outcome [201].…”
Section: Mtor At the Cross-road Between Diabetes And Cancermentioning
confidence: 99%